ANALYSIS OF SACHET WATER, BOTTLED WATER AND BOREHOLE WATER CONSUMED IN AND AROUND ANAMBRA STATE POLYTECHNIC, MGBAKWU - C.F. , Ezeama,; C.C., Achonye, (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Water is an inorganic, odourless, tasteless, transparent, and nearly colourless chemical substance made up of hydrogen and oxygen existing in gaseous, liquid, and solid states (Zumdahl, 2020). About 1.2 billion people worldwide do not have access to clean, safe water, and most of them are in developing countries (Amaechi, 2016). Unsafe water quality is a global public health issue. There is concern that borehole, sachet water and bottle water produced in developing nations may be sold without adequate monitoring, and that water treatment may be subject to contamination. The purpose of this quantitative study was to examine the level of contamination of drinking water sourced from boreholes, bottle water and sachet-packaged water around Anambra State Polytechnic, Mgbakwu, Southeast Nigeria. Local officials may utilize this study's results to develop a standard that can improve the quality of commercially packaged, bottle water, sachet and borehole water for drinking purposes